Long life learning preparing for jobs that don't even exist yet - Weise, Michelle R. (Tantor Media, Inc., 2022)
A visionary guide for the future of learning and work Long Life Learning: Preparing for Jobs That Don't Even Exist Yet offers listeners a fascinating glimpse into a near-future where careers last 100 years, and education lasts a lifetime. The book makes the case that learners of the future are going to repeatedly seek out educational opportunities throughout the course of their working lives-which will no longer have a beginning, middle, and end. Long Life Learning focuses on the disruptive and burgeoning innovations that are laying the foundation for a new learning model that includes clear navigation, wraparound and funding supports, targeted education, and clear connections to more transparent hiring processes. Written by the former chief innovation officer of Strada Education Network's Institute for the Future of Work, the book examines: - How will a dramatically extended lifespan affect our careers? - How will more time in the workforce shape our educational demands? - Will a four-year degree earned at the start of a 100-year career adequately prepare us for the challenges ahead?
Online resource; title from title details screen (O'Reilly, viewed October 4, 2022)
Keywords: Employees -- Training of; Career education; Occupational training; Vocational education; Manpower planning; Personnel; Formation; Préparation à une carrière; Enseignement professionnel; Main-d'uvre; Planification; Employees; Training of; Audiobooks; Livres audio